2010
DOI: 10.1002/jbmr.208
|View full text |Cite
|
Sign up to set email alerts
|

Osteoblast-specific expression of MEF induces osteopenia through downregulation of osteoblastogenesis and upregulation of osteoclastogenesis

Abstract: In bone remodeling, various transcriptional factors are involved, and the deficiency or overexpression of some of these factors results in bone defects. Myeloid elf-1-like factor (MEF) is one of the Ets transcription factors that control the expression of genes that are critical for biologic processes such as cell proliferation, differentiation, and death. Previously, we reported that MEF promotes cell proliferation and functions as a negative regulator of osteogenic differentiation by interacting directly wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…34 After implanting the chitosan nanofiber scaffolds into the bone defect sites for 21 days, the animals were sacrificed, and the femurs were collected. After removing the muscle and connective tissues, the femurs were weighed and photographed.…”
Section: Microcomputed Tomographymentioning
confidence: 99%
“…34 After implanting the chitosan nanofiber scaffolds into the bone defect sites for 21 days, the animals were sacrificed, and the femurs were collected. After removing the muscle and connective tissues, the femurs were weighed and photographed.…”
Section: Microcomputed Tomographymentioning
confidence: 99%
“…Thus, we focused on the regulatory mechanisms of MEF on MAB21L1 transcription in osteoblast cells. Because MEF appeared to be a negative regulator of osteoblast differentiation in our previous studies [Kim et al, 2007; Seul et al, 2011], we speculated that MAB21L1 , which is up‐regulated by MEF, could also be involved in suppressing several catabolic osteogenic factors in the osteoblast differentiation process.…”
Section: Resultsmentioning
confidence: 99%
“…Over‐expression of MEF suppresses the expression of osteogenic related genes, such as ALP, Dlx5, OP, and OC, which are required for the terminal differentiation of an osteoblast. Moreover, osteoblast‐specific expression of MEF induced osteopenia through down‐regulation of osteoblastogenesis and up‐regulation of osteoclastogenesis [Seul et al, 2011]. Furthermore, our unpublished data also showed that overexpression of MEF or Mab21 could induce apoptosis of MG63 osteoblastic cells by increasing the level of cleaved caspase‐3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ELF4 also regulates self-renewal of braintumor stem cells (Bazzoli et al, 2012). In addition, ELF4 plays an important role in osteogenic differentiation and bone development (Kim et al, 2007;Seul et al, 2011;Baek et al, 2012). It mediates DNA damage response (Morales et al, 2008;Sashida et al, 2011).…”
Section: Elf4 (E74-like Factor 4 (Ets Domain Transcription Factor))mentioning
confidence: 99%